Nutrition intake, insulin-like growth factor-1 hormone levels, somatotype score, and strength performance of adolescent athletes - Zetta, Adelia Paradya; Susanto, Hardhono; Noer, Etika Ratna; Muniroh, Muflihatul; Widyastiti, Nyoman Suci (UIR Press, 2024)
Background Problems: Currently, there is still limited identification of nutritional intake, hormonal, and physical performance in adolescent athletes in Indonesia. Research Objectives: This study aims to identify anthropometric, nutritional intake, IGF-1 hormone level, and adolescent athletes’s performance. Methods: The research method used a cross-sectional study. A convenient sample of 58 athletes under Balai Pemusatan Pendidikan dan Latihan Pelajar. The research instrument used Bioelectrical Impedance Analysis (BIA), leg dynamometer, hand grip dynamometer, tape measure, height stature, SQ-FFQ Form, and body fat caliper. Blood samples were collected and tested by a professional laboratory. Data analysis techniques used Pearson’s test for normally distributed data and Spearman’s rank for non-normally distributed data. Findings and Results: The result of this study found a significant (p < 0.05) correlation between energy intake, anthropometric measurement of z score (BMI/Age), and endomorph score with an athlete’s muscle strength. We also found significant differences (p < 0.05) in macronutrient and micronutrient consumption in male and female athletes, and we also found significant differences in somatotype score and muscle strength in male and female athletes. Conclusion: We conclude that many athletes are not consuming the recommended levels of carbohydrates, fat, protein, and some micronutrients. We found a correlation between energy intake and fat intake with leg muscle strength. However, there was no correlation between IGF-1 hormone levels and athlete strength. Intake is thought to indirectly affect grip strength and leg strength.